2020
DOI: 10.1111/ppl.13168
|View full text |Cite
|
Sign up to set email alerts
|

Priming of tomato seedlings with 2‐oxoglutarate induces arsenic toxicity alleviatory responses by involving endogenous nitric oxide

Abstract: Metal toxicity in crop plants is a matter of scientific concern. Therefore, in recent years efforts have been made to minimize metal toxicity in crop plants. Out of various strategies, priming of seedlings with certain chemicals, like e.g. donors of signaling molecules, nutrients, metabolites or plant hormones has shown encouraging results. However, mechanisms related with the priming‐induced mitigation of metal toxicity are still poorly known. Hence, we have tested the potential of 2‐oxoglutarate (2‐OG) primi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 78 publications
3
10
0
Order By: Relevance
“…Our findings suggest that AKG supplementation significantly enhances growth parameters in poplar Nanlin 895 under high ammonium levels, evidenced by notable increases in height and biomass (Figure 1). These observations were in alignment with prior reports that demonstrate the growth-promoting effects of exogenous AKG application in various crops [19,20,[22][23][24][25][26][27], implying that the role of AKG in ammonium detoxification is conserved in different organisms.…”
Section: Application Of Akg Promotes Ammonium Assimilation In Poplars...supporting
confidence: 91%
See 2 more Smart Citations
“…Our findings suggest that AKG supplementation significantly enhances growth parameters in poplar Nanlin 895 under high ammonium levels, evidenced by notable increases in height and biomass (Figure 1). These observations were in alignment with prior reports that demonstrate the growth-promoting effects of exogenous AKG application in various crops [19,20,[22][23][24][25][26][27], implying that the role of AKG in ammonium detoxification is conserved in different organisms.…”
Section: Application Of Akg Promotes Ammonium Assimilation In Poplars...supporting
confidence: 91%
“…Plants utilize two primary pathways for ammonium assimilation: the GS/GOGAT cycle and the GDH-mediated reaction [14,38]. Our investigation showed that AKG administration led to a decrease in GDH and AspAT activities in the leaves (Figure 4c,d), akin to findings in tomato plants [23], indicating that the GDH-mediated reaction is a low ammonium affinity pathway [40] in poplars treated with AKG under high ammonium stress. By contrast, exogenous AKG enhanced the expression of PtrGS1 and PtrGS2 (Figure 9b) and stimulated GS/GOGAT enzyme activities in the leaves (Figure 4a,b), suggesting that the GS/GOGAT cycle is preferential for AKG-mediated ammonium detoxification in poplars.…”
Section: Application Of Akg Promotes Ammonium Assimilation In Poplars...supporting
confidence: 57%
See 1 more Smart Citation
“…Fukudome, Watanabe, Osuki, Uchi, and Uchiumi (2019) reported endogenous NO increases during root‐nodule symbiosis of Lotus japonica using DAF‐FM DA. Visualization of NO was performed during arsenic toxicity in tomato roots using DAF‐2DA (Alamri et al., 2021). Thymol increased the NO in tobacco seedlings as measured by DAF‐FM DA (Xu et al., 2022).…”
Section: Commentarymentioning
confidence: 99%
“…Differential respiration responses, namely, extensive metabolite content changes, are among the common responses of plants to As toxicity (Saini et al, 2023). 2-oxoglutarate dehydrogenase complex (2-OGDC) is a key metabolic enzyme necessary for the cyclic operation of the TCA cycle (Alamri et al, 2021). This enzyme is found to be one of the prime targets of metalloids and is physiochemically inhibited by them (Wei et al, 2022).…”
mentioning
confidence: 99%